Impact of Corona Virus on Criminal Action and Prevention Measures in Indonesia - I Ketut Seregig; Bambang Hartono; Budi Waskito (Sociological Jurisprudence Journal, 2020)
This article is data obtained from interviews with traders in traditional and modern markets about the impact of criminal acts due to the corona virus outbreak in Indonesia. The data is supported by secondary data collected from official sources, among others published by the ministry of trade and other social media. The purpose of writing this article is to provide input on a corona virus epidemic prevention plan and mitigate the impact of criminal acts due to hoax news related to corona virus outbreaks. The impact of the corona virus outbreak in the community is the accumulation of protective masks that cause the price of masks to rise in the market, the spread of hoaxes by people who are not responsible, among others; hoax news with the contents "corona virus cannot stand the heat", and "red ginger, kaempferiagalanga, curcuma, pepper are considered as drugs that can fight the corona virus" which results in an increase in the price of rhizomes and spices and is becoming rare in the traditional market. The stakeholders under the coordination of the Coordinating Ministers undertook strategic actions including the National Police and the Ministry of Health and the Regional Head who carried out market operations for the distribution of masks, ginger and spices distribution in traditional markets. As a result, the team formed by the National Police, assisted by the Ministry of Health, succeeded in capturing mask hoarders in the Jakarta area. The hoarders are prosecuted by carrying out law enforcement and bringing the perpetrators to justice.